Connectedness, engagement, and learning through social work communities on LinkedIn - Castillo-de Mesa, Joaquín (Colegio Oficial de Psicólogos de Madrid, 2020)
Social networking sites have enabled a high connectedness leading to unprecedented interactive dynamics. Social workers are using these digital means and are generating communities of practice through which they cooperate and share information. Through netnography and analysis of social networking sites we have observed the presence, identity, and connectedness, and interaction patterns on LinkedIn of 170 social workers who worked at 41 organizations from specific contexts. Implicit communities were identified through various algorithms, thus analyzing leadership and cohesion of their members. Results show connectedness and interaction patterns that lead to the creation of communities of practice on LinkedIn based on social work domains and practices. The possibility of establishing and maintaining relationships on LinkedIn and applying social networking sites to social intervention as an innovative strategy to improve information exchange and cooperation between professionals and organizations is addressed in the discussion.